A qualitative exploration of perceived challenges and opportunities in the implementation of injury prevention and management in amateur female sport - Walshe, Ayrton; Daly, Ed; Ryan, Lisa (Frontiers in Sports and Active Living, 2024)
Introduction: Coaches, practitioners, and leadership in amateur female sport must navigate many obstacles in the pursuit of athlete availability and optimal performance. The present study aims to evaluate opportunities and challenges to both injury prevention and management in amateur female sport, as experienced by mixed-gender coaches, allied healthcare professionals, and general practitioners.Methods: Semi-structured virtual interviews of coaches, allied healthcare professionals and general practitioners (N = 25), recruited via convenience snowball sample. Data transcribed verbatim with reflexive thematic analysis through a critical realism framework.Results: Female-specific issues, education, and resource capital were challenges to the implementation of injury prevention and management sport science and medicine in amateur female sport thus negatively impacting on performance, injury prevention, and rehabilitation. Opportunities for improved care for female athletes were communication and relationships, outsourcing responsibility, and despite the lack of education; desires for such, and lastly exposure to elite sport and national governing bodies protocols.Discussion: In amateur female sport, developing communication pathways and relationships, along with upskilling coaches can help better support female athletes, coaches, and healthcare professionals. Leaders and stakeholders must advocate for and support greater education, resourcing and an understanding of female-specific issues in amateur female sport. It is intended that these findings provide evidence and opportunities for discourse between stakeholders in amateur female sport to improve standard of supports for female athletes, coaches and healthcare professionals. Findings may also help practitioners better exploit opportunities and circumvent challenges to improve welfare and performancecare of amateur female athletes.